Polyphenols in health and food processing: antibacterial, anti-inflammatory, and antioxidant insights - Sun, Shengqian; Liu, Zhengyang; Lin, Mingxia; Gao, Na; Wang, Xiaojie (Frontiers in Nutrition, 2024)
Polyphenols, as subordinate metabolites of plants, have demonstrated significant antibacterial, anti-inflammatory, and antioxidant action in scientific learn. These compounds exert their effects through various mechanisms, containing interference with microbial cell structures, rule of host immune responses, and neutralization of free radicals. This multifaceted activity positions polyphenols as promising candidates for maintaining human health and treating related diseases. Notably, in the context of escalating antibiotic resistance, the antibacterial properties of polyphenols offer innovative avenues for the development of new therapeutic agents. Additionally, their anti-inflammatory and antioxidant effects hold substantial potential for treating inflammatory diseases and mitigating the aging process. This review aims to summarize the latest findings on the biological activities of polyphenols, highlighting their mechanisms of action and potential applications in health and disease management. Furthermore, optimizing polyphenol extraction methods aligns with the goals of sustainable and green processing, reducing environmental impact while enhancing food safety and extending shelf life.Employing advanced analytical techniques, such as spectroscopy and chromatography, can ensure the accurate evaluation of polyphenol content and efficacy. These efforts collectively contribute to the ongoing improvement of food processing practices and product quality, promoting a healthier and more sustainable future in the food industry.